(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2023)
The Rhamphosidae is an extinct family of syngnathiform fishes from the lower Eocene deposits of Europe, primarily known from specimens derived from the Ypresian Konservat-Lagerstätte of Bolca (Verona province, Italy). A descriptive analysis of 28 specimens of Rhamphosus from Bolca revealed the existence of six species, showing a greater taxonomic diversity compared to the previous scenario of only two species (the type species Rhamphosus rastrum and Rhamphosus biserratus). Four new species are established herein: Rhamphosus bloti n. sp., characterized by a peculiar and unique rostrum with a discoid shape; Rhamphosus brevirostris n. sp., which exhibits a moderately large size associated with a relatively short rostrum; Rhamphosus longispinatus n. sp., characterized by having the longest dorsal-fin spine and rostrum of all the Rhamphosus species; Rhamphosus tubulirostris n. sp., which shows a peculiar slim rostrum, long-based dorsal and anal fins, and a unique squamation characterized by the presence of numerous bucklers. The species from Bolca are also compared to the only other known Rhamphosus species, Rhamphosus rosenkrantzi, from the Fur Formation, Denmark. A number of morphological features support the assignment of the Rhamphosidae to the syngnathiform clade Dactylopteroidei, together with the extant families Dactylopteridae and Pegasidae, representing the sister group to the Pegasidae.